Credit Transaction Analysis of "Pagang Gadai" Model as Sharia Law Implementation in West Sumatera: A Systematic Literature Review - Yulhendri; Lukman Hakim; Mentari Ritonga; Rani Sofya; Nora Susanti; Muhammad Rizki Prima Sakti (al-Uqud : Journal of Islamic Economics, 2021)
"Pagang gadai" transaction has become a sociocultural activity for Minangkabau society in West Sumatera. This transaction has been entrenched and rooted in life. However, over time, this activity has begun to change from its initial values, as a principle of helping each other and a cultural tradition, to an economic motive, namely a business transaction, which then turns into a commercial value. Several studies have indicated that "pagang gadai" is no longer merely applying the principle of helping each other and a cultural activity, but has an economic motive, that is a shifting pattern that leads to the hold over wealth from one person to another in order to obtain financial benefits. This transaction allows the pawnbroker to hold productive agricultural land, such as rice fields, fish ponds, yards, coconut trees, and even cars. The right-of-use land and productive assets then belong to the lender. So, some research and empirical studies indicate that "pagang gadai" no longer has a social value but begins to partially change into usury. Therefore, it is better for the society to go back to the foundation of adat philosophy "syarak mangato adat memakai", and the application of state law should be consistent as Government Regulation in Lieu of Law No.56/1960 about the use of agricultural land in Article 7 limits the period of "pagang gadai" to 7 years and the agricultural land is handed back without ransom.